Flexible Work in E-Commerce: Impact on Engagement Mediated by Satisfaction and Work-Life Balance - Lapian, Nessa Desnari; Purba, Sylvia Diana (KINERJA, 2026)
This study was conducted to determine the application of flexible working arrangements for employee engagement, mediated by work-life balance and job satisfaction, in E-Commerce industry. The method employed was purposive sampling as a technique to determine the sample. This study was conducted by distributing Google Form questionnaires using a Likert scale to employees in the E-Commerce industry who are currently or have previously worked under hybrid or flexible working arrangements. Data were collected from 129 respondents and processed using SmartPLS 4.1 software. The criteria in this study are employees who are currently or have previously worked under hybrid or flexible working arrangements in the e-commerce industry. The research offers practical insights for optimizing flexible working arrangements in the e-commerce industry. The findings can guide companies in enhancing policy implementation through clear work guidelines, structured reward systems, employee training, and a strong feedback culture—ultimately improving employee engagement and the quality of human resources.